Real-life experience with first-line treatment with daratumumab, bortezomib, melphalan, and prednisone in patients with newly diagnosed multiple myeloma ineligible for autologous stem-cell transplantation - Domingo-González, Amalia; Alonso Fernández, Rafael; Jiménez, Ana; De Soto Álvarez, Teresa; Lerma-Verdejo, Ana; Pradillo, Virginia; Benzo Callejo, Gonzalo; Sánchez-Pina, Jose; Landete, Elena; Velasco-Valdazo, Alberto; Menéndez-Cuevas, Marina; López Riñón, Mónica María; et al. (Frontiers in Hematology, 2024)
IntroductionThe regimen with daratumumab, bortezomib, melphalan, and prednisone (D-VMP) is one of the recommended treatments for newly diagnosed multiple myeloma (NDMM) non-transplant eligible due to the results described in the ALCYONE trial. However, real-life outcomes with this regimen are limited. This study assesses the real-life effectiveness and safety of this regimen.MethodsWe retrospectively analyzed the data on efficacy, safety, and survival parameters of D-VMP regimen in 112 patients with NDMM not eligible for autologous stem-cell transplantation with attention to the effect of age, R2-ISS, high-risk cytogenetic abnormalities (CA), and depth of response.ResultsPatients aged ≥75 years constituted 70% of our cohort. Fifty-two percent had R2-ISS 3-4, and 60% had high-risk CA. Twenty-three percent of patients would have been excluded from the ALCYONE trial. After a median follow-up of 31.4 months, all patients had completed induction, with a median number of cycles of 9 (IQR 6-9). The overall response rate was 95%, and 72% achieved very good partial response (VGPR) or better. The median progression-free survival (PFS) was 41.5 (95% CI, 34.3 to NE), and the median overall survival (OS) was not reached. The most frequent adverse event (AE) was neuropathy (27%), followed by gastrointestinal symptoms (13%) and hematological AE (10%). Age did not negatively impact survival outcomes. Patients with ≥2 high-risk CA or those who achieved <VGPR had a worse OS (p= 0.026 and p= 0.030). After performing multivariate analysis, we didn’t find statistically significant prognostic factors for PFS or OS.DiscussionIn real-life practice, the D-VMP combination showed a similar efficacy and safety profile to those reported in the ALCYONE and OCTANS trials.